2008
DOI: 10.1111/j.1542-474x.2008.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Signal‐Averaged Analysis of Atrial Electromagnetic Characteristics in Patients with Paroxysmal Lone Atrial Fibrillation

Abstract: Clinical subclasses of lone AF seem to possess distinct signal profiles of atrial depolarization. Differences in electrophysiological properties between these subclasses may reflect pathogenetic variation and could have implications on diagnostics and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The same findings apply when analysis is restricted to “lone” paroxysmal AF patients, suggesting that even in this specific subgroup, some electrical abnormalities are present making the term “lone” inadequate and obsolete. These results are in agreement with previous studies showing significant modifications in P-wave morphology [8], altered atrial conductive properties [6], [13], [14], [15], [16], prolonged regional refractoriness [14], increased atrial dispersion of refractoriness [17] and shortening of atrial refractory periods [18], in patients with paroxysmal “lone” AF. It has also been shown that these patients have evidence of atrial fibrosis on magnetic resonance imaging [19].…”
Section: Discussionsupporting
confidence: 93%
“…The same findings apply when analysis is restricted to “lone” paroxysmal AF patients, suggesting that even in this specific subgroup, some electrical abnormalities are present making the term “lone” inadequate and obsolete. These results are in agreement with previous studies showing significant modifications in P-wave morphology [8], altered atrial conductive properties [6], [13], [14], [15], [16], prolonged regional refractoriness [14], increased atrial dispersion of refractoriness [17] and shortening of atrial refractory periods [18], in patients with paroxysmal “lone” AF. It has also been shown that these patients have evidence of atrial fibrosis on magnetic resonance imaging [19].…”
Section: Discussionsupporting
confidence: 93%
“…In view of this result, it could be considered that P wave high‐frequency energy analysis could provide additional morphological information to the one revealed by its duration. This finding is clinically relevant because recent works have suggested that P wave duration alteration could not be considered as an unavoidable requirement for AF development To this respect, previous works have shown that patients with lone PAF failed to demonstrate any remarkable P wave prolongation . Similarly, P wave duration has not been predictive of new‐onset AF in patients with congestive heart failure …”
Section: Discussionmentioning
confidence: 90%
“…PW prolongation is generally accepted as the most reliable noninvasive marker of atrial conduction and it has been associated with a history AF . However, several studies failed to demonstrate significant PW prolongation in patients with AF, and shorter PW duration has been associated with lone AF, suggesting that locally delayed intra‐ and interatrial conduction rather than global conduction slowing may occur. Accordingly, Josephson et al first suggested that biphasic PWs in the right precordial leads may represent an interatrial conduction defect not necessarily associated to left atrial enlargement.…”
Section: Discussionmentioning
confidence: 99%